The Role of Host Genetics Regulating Proteins in HIV-1 Susceptibility: Epidemiological and Demographic Insights on HIV-1 in Indonesia (2022) - Saefudin, Siti Amalia Firdza; Handayani, Niken Satuti Nur (Institute of Topical Disease Universitas Airlangga, 2024)
Human Immunodeficiency Virus type 1 (HIV-1) remains a global public health concern, marking 52,995 cases in Indonesia alone, dominated with CRF01_AE strain which is classified as an X4 strain or a virus that uses CXCR4 co-receptor. This highlights the urgent needs to develop therapies that utilize CXCR4 inhibitors to modulate HIV-1 infection and replication. The aims of this study were to assess the epidemiological and demographic insights on HIV-1 in Indonesia in 2022, and connecting it to the dominated strain to further assess various host genetics known to promote HIV-1 infection, focusing on the co-receptors CCR5 and CXCR4. A systematic review was conducted, analyzing published studies and the 2022 HIV/AIDS report from the Ministry of Public Health of Indonesia. Additionally, the study evaluated the therapeutic potential of CXCR4 antagonists, including AMD3100, AMD070, BPRCX807, and MCo-CVX-5c, known for their anti-HIV-1 activity. Among the listed antagonists, AMD070 and MCo-CVX⎯5c are advancing among the others, leading to a potential most advanced combination antiretroviral therapy (cART). This research contributed to the development of personalized treatment strategies for HIV-1 by providing insights into the genetic factors influencing co-receptor regulation and HIV-1 susceptibility.